Methylation profiles of genomic DNA of mouse developmental brain detected by restriction landmark genomic scanning (RLGS) method - Jun Kawai; Shinji Hirotsune; Kenji Hirose; Shinji Fushiki; Sachihiko Watanabe; Yoshihide Hayashizaki (1993)
Restriction landmark genomic scanning using methylation-sensitive endonucleases (RLGS-M) is a newly developed powerful method for systematic detection of DNA methylation. Using this method, we scanned mouse brain genomic DNAs from various developmental stages to detect the transcriptionally active regions. This approach is based on the assumption that CpG methylation, particularly of CpG islands, might be associated with gene transcriptional regulation. Genomic DNAs were prepared from telencephalons of 9.5-, 13.5- and 16.5-day embryos, 1- and 10-day neonates and adults, followed by subjecting them to RLGS-M and comparing their patterns with each other or with that of the adult liver. We used Notl as a methylation-sensitive restriction enzyme and surveyed the methylation states of 2,600 Notl sites, almost of which should correspond to gene loci. Although almost all RLGS spots (98%) were present constantly at every developmental stages, only a few percent of spots reproducibly appeared and disappeared at different developmental stages of the brain (44 spots, 1.7%) and some were tissue-specific (10 spots, 0.7%). These data suggest that DNA methylation associated with gene transcription is a well-programmed event during the central nervous system (CNS) development. Thus, RLGS-M can offer a means for detecting systematically the genes in which the state of DNA methylation changes during development of the higher organism.